2006
DOI: 10.1134/s000629790604016x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hypermethylation of CCWGG sequences in DNA of Mesembryanthemum crystallinum plants on their adaptation to salt stress

Abstract: Under salt stress conditions, the level of CpNpG-methylation (N is any nucleoside) of the nuclear genome of the facultative halophyte Mesembryanthemum crystallinum in the CCWGG sequences (W = A or T) increases two-fold and is coupled with hypermethylation of satellite DNA on switching-over of C3-photosynthesis to the crassulacean acid metabolism (CAM) pathway of carbon dioxide assimilation. The methylation pattern of the CCWGG sequences is not changed in both the 5'-promoter region of the gene of phosphoenolpy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(54 citation statements)
references
References 9 publications
2
48
0
2
Order By: Relevance
“…Selective hypermethylation on salt stress adaptation in the extremophile Crassulacean acid metabolism (CAM) plant Mesembryanthemum crystallinum , for example, indicates both specific and global epigenetic restructuring in plant abiotic stress response regulation [57]. …”
Section: Epigenetic Modifications and Non-coding Rnasmentioning
confidence: 99%
“…Selective hypermethylation on salt stress adaptation in the extremophile Crassulacean acid metabolism (CAM) plant Mesembryanthemum crystallinum , for example, indicates both specific and global epigenetic restructuring in plant abiotic stress response regulation [57]. …”
Section: Epigenetic Modifications and Non-coding Rnasmentioning
confidence: 99%
“…Several other papers suggest that changes in DNA methylation are required for stress protection. Dyachenko et al [2006] demonstrated a two-fold increase in CpNpG methylation level in nuclear genome of M. crystallinum plants exposed to high salinity conditions. The increase in methylation was associated with switching from C3-photosynthesis to CAM metabolism.…”
Section: Dna Methylation Is the Primary Epigenetic Markmentioning
confidence: 99%
“…For example, exposure to salt promotes DNA methylation in Mesembryanthemum crystallinum through the enhancement of DNA methyltransferase activity (Dyachenko et al, 2006). In addition, the genomes of some saline-tolerant cotton cultivars are hyper-methylated in comparison with the genomes of salinesusceptible cultivars (Wang et al, 2015a).…”
Section: Discussionmentioning
confidence: 99%